Towards an United Approach to the Practice of Ozone Therapy Worldwide (Ozone Therapy Global Journal, 2015)
This is the slogan of the "International Meeting of the Madrid Declaration on Ozone Therapy (2nd. Ed.), which ISCO3 (International Scientific Committee of Ozone Therapy) is organizing in Madrid this 12 June.The Spanish Journal of Ozone Therapy (Revista Española de Ozonoterapia) joins this important event which marks a very important milestone in the history of ozone therapy.In the International Meeting ISCO3 will present the updated Madrid Declaration. Process that began a year ago when ISCO3 members decided that after five years in force it was time to update its content by incorporating scientific advances related to ozone.For its updating a worldwide call to ozone therapists was made asking them to submit their proposals for amendments. Taken into account the high number of proposals received, the contributions of ISCO3 experts, and after additional intense months of writing several drafts, the final text was approved by ISCO3.